Health Related Quality of Life (HRQoL) of school teacher at Perak Tengah: a case study on the secondary school in urban and rural area / Sharifah Nur Aliah Syed Azelan, Nurul Nazatulnazua Kamarudin and Nurfashihah Ahmad Kharmain - Syed Azelan, Sharifah Nur Aliah; Kamarudin, Nurul Nazatulnazua; Ahmad Kharmain, Nurfashihah (2019)
Teaching and learning are common things that were related to each other. Teachers are the person who teaches about knowledge and inspires students to study especially at school. Their work is not limited in teaching, but they also need to participate in curricular activities at school. Thus, teaching is a stressful profession. This study reports on the health-related quality of life (HRQoL) problems among teachers of urban and rural schools in Perak Tengah. The purpose of this study was to determine the relationship between work stress at school with Mental and Physical Health of secondary school teachers. A cross-sectional study was conducted in secondary school in Perak Tengah where 80 out of 96 teachers were selected by using stratified random sampling. Self-Administered Short Form 36 version 2 (SF-36v2) questionnaires in bilingual version was used. The response rate 38 respondents were urban secondary school teachers and 42 respondents were rural secondary school teachers. Descriptive analyses, independent samples t-test and multiple linear regression were used to analyze the data. It was found that the HRQoL of secondary school teachers are lower than the General Malaysian population norms for all the eight domains except for General Health and Bodily Pain. The result also showed that there are no significant different for eight domains between urban and rural secondary schools teachers. Five variables are significantly contributed to Physical Health which are age, gender, marital status, appointment as classroom teacher and extra class involvement. In addition, age, gender, educational level, appoinment as classroom teacher and extra class involvement are the factors that significantly affect the Mental Health. Based on the result, the researchers suggest the school's management to shorten the distance of the teacher's room with classroom for teachers who have physical problem. Other than that, school's management also should limit the working hours especially on Saturday and Sunday in order to increase their Mental Health.